Characterization of intravascular cellular activation in relationship to subclinical atherosclerosis in postmenopausal women - Jayachandran, Muthuvel (PLoS One, 2017)
OBJECTIVE: Mechanisms and interactions among intravascular cells contributing to development of subclinical atherosclerosis are poorly understood. In women, both menopausal status and pregnancy history influence progression of atherosclerosis. This study examined activation and interactions among blood elements with subclinical atherosclerosis in menopausal women with known pregnancy histories. METHODS: Carotid intima-media thickness (CIMT), as a marker of subclinical atherosclerosis, was measured using B-mode ultrasound in age- and parity-matched women [40 with and 40 without a history of preeclampsia] 35 years after the index pregnancy. Interactions among intravascular cells (38 parameters) were measured by flow cytometry in venous blood. Data analysis was by principal component which retained 7 independent dimensions accounting for 63% of the variability among 38 parameters. RESULTS: CIMT was significantly greater in women with a history of preeclampsia (P = 0.004). Platelet aggregation and platelet interactions with granulocytes and monocytes positively associated with CIMT in postmenopausal women independent of their pregnancy history (ρ = 0.258, P< 0.05). However, the association of the number of platelets, platelet activation and monocyte-platelet interactions with CIMT differed significantly depending upon pregnancy history (test for interaction, P<0.001). CONCLUSION: Interactions among actived intravascular cells and their association with subclinical atherosclerosis differ in women depending upon their pregnancy histories.